2016
DOI: 10.7314/apjcp.2016.17.2.479
|View full text |Cite
|
Sign up to set email alerts
|

Do VDR Gene Polymorphisms Contribute to Breast Cancer?

Abstract: Breast cancer is the first or second leading cancer among females across the globe. A large number of studies have been conducted to assess any relationship between vitamin D receptor (VDR) gene polymorphisms and breast cancer development. Epidemiological studies have indicated that ethnic traits exhibited by a group of people with a common ancestry and culture, alter the link between VDR gene and breast cancer. It has been hypothesized that VDR polymorphisms have the capacity to impact both on incidence of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
17
0
6
Order By: Relevance
“…Moreover, many recent reports found a marked increased susceptibility to breast cancer between women carrying ApaI GG genotype compared with women carrying genotype TT. 4,9,37,50 On the contrary, McCullough et al and Mishra et al reported no significant relation between the ApaI variants and breast cancer prevalence among Indian and Caucasian women. 32,49,[51][52][53] Interestingly, our findings indicated the existence of marked difference between patients and control samples of women carrying TC genotype of VDR TaqI (rs731236).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many recent reports found a marked increased susceptibility to breast cancer between women carrying ApaI GG genotype compared with women carrying genotype TT. 4,9,37,50 On the contrary, McCullough et al and Mishra et al reported no significant relation between the ApaI variants and breast cancer prevalence among Indian and Caucasian women. 32,49,[51][52][53] Interestingly, our findings indicated the existence of marked difference between patients and control samples of women carrying TC genotype of VDR TaqI (rs731236).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heterogeneity by tumor subtype was also seen for rs1544410, rs7967152 and rs2239186 VDR polymorphisms in Europeans (30). These case-control and meta-analysis studies suggest that VDR polymorphism may be associated with increased risk of breast cancer (Table I) and poly(A) on development of breast cancer from 1996 to 2015 and suggested that due to the inconsistent results of various studie, no conclusive evidence associates the risk of breast cancer with VDR polymorphism (32). Similarly, the inconsistent results of the studies shown in Table I suggest the need for further research.…”
Section: Female Reproductive Tract Cancermentioning
confidence: 98%
“…25 BsmI but not Fok1 was associated with the risk of breast cancer among Iranian women. 49 However, Shaikh et al 50 in their mini review compare the impact of VDR gene polymorphisms, Fok1, Bsm1, Taq1, Apa1, and poly(A), on the development of breast cancer and showed inconsistent results, with no conclusive statements about the significance of the VDR genotype on breast carcinoma development ( Table 2).…”
mentioning
confidence: 99%